HEALTH TECHNOLOGIES AND TECHNOLOGICAL APPROACH IN THE EDUCATIONAL PROCESS - Kuznietsova, Olena (European Science, 2025)
Based on the analysis of 30 pedagogical works, various scientific approaches to defining the concepts of "pedagogical technology", "educational technology", "teaching technology", "management technology", "health-preserving technologies" and "health techn